Clear Cell Carcinoma Arising from Cesarean Section Scar Endometriosis: Case Report and Review of the Literature - Sakura Ijichi; Taisuke Mori; Izumi Suganuma; Takuro Yamamoto; Hiroshi Matsushima; Fumitake Ito; Makoto Akiyama; Izumi Kusuki; Jo Kitawaki (Hindawi Limited, 2014)
Introduction. The incidence of endometriosis affecting skin tissue represents only 0.5-1.0% of all endometriosis cases. A malignancy in the abdominal wall arising from endometriosis following cesarean section is even rarer; only 21 cases have previously been reported. The therapeutic strategy has not been determined because of the limited cases. We report a case of clear cell adenocarcinoma arising in the abdominal wall from endometriosis tissues following cesarean section and review previous literature to achieve the optimal treatment and better prognosis. Case Presentation. A 60-year-old woman presented with a growing mass at the left side of a cesarean section scar. Radical resection of the abdominal wall mass was performed. Histopathological examination showed a clear cell adenocarcinoma. Benign endometrium-like tissues were found adjacent to the cancer lesion in the excised specimen, suggesting malignant transformation from endometriosis of the abdominal wall. Discussion. Local resection was performed in 10 cases (47.6%) and total abdominal hysterectomy or oophorectomy was conducted in 11 cases (52.4%). No malignant lesions were observed in either the uterus or adnexa that were resected. These cases may be expected to increase with increasing incidence of cesarean section. The significance of the extensional resection should be further elucidated.